Quality and content analysis of female urethroplasty videos on YouTube. Issue 1 (31st October 2022) - Sahin, Yusuf; Paslanmaz, Filip; Ulus, Ismail; Yilmaz, Mehmet; Dincer, Muhammet Murat; Muslumanoglu, Ahmet Yaser
Abstract: Objectives: In this study, we aimed to analyze scientific quality and content of female urethroplasty videos on YouTube. Methods: We searched YouTube using the "female urethroplasty", "female urethral stricture", and "urethroplasty" keywords on February 22, 2022. The quality and content of videos were analyzed using the Global Quality Score (GQS) and Female Urethroplasty‐Specific Checklist Score (FUSCS) which was developed by our clinic. Video analysis was performed by two independent urologists. The relationship between the video characteristics and GQS and FUSCS was examined. Results: A total of 38 videos were analyzed. Fourteen (36.8%) videos were uploaded by academic sources such as urology societies and universities/hospitals, while 24 (63.2%) videos were uploaded by urologists. The median GQS was 3 (range, 2–4) and the median FUSCS was 8 (range, 5–9) for all videos. The Cohen's kappa was 0.834 for GQS and 0.899 for FUSCS, indicating a high level of agreement between the observers. The median GQS was 4 (range, 4–5) and the median FUSCS was 9 (range, 8–10) for academic videos, indicating a statistically significantly higher scores than the urologists videos ( p  = .002 and p  < .001, respectively). Conclusion: Academic videos on female urethroplasty on YouTube have adequate scientific quality and content for both patients and healthcare professionals. The number of videos by academic sources on female urethroplasty should be increased and individuals should be encouraged to search such videos on search engines.